COVID-19, “Roll Camera and Action”: Filming culture of a Ghanaian Cinematographer in a Pandemic Era - Brako, Daniel Kofi (Research Journal in Advanced Humanities, 2022)
With the outbreak of the COVID-19 pandemic, filmmaking and filmmakers have been affected most across the globe. Predominantly, it has not only changed execution of the role of Cinematographers on film sets during the filmmaking process, but also has certain repercussions on the profession as far as filmmaking is concerned. Based on this situation, this study examines how Ghanaian Cinematographers observe protocols on set when filming during the pandemic. In addition, it considers some effects of COVID-19 pandemic on the Cinematography profession in this part of our world as far as filmmaking is concerned. Findings indicate that personal hygiene, which was disregarded during filming in the past has now become a daily ritual before a camera roll on film sets. It is noted that in spite of some participants being cautious during filming on set caught the disease in one way or the other. Despite its negative effects, it has also introduced various avenues that serve as new opportunities to enhance the Cinematography profession locally. Also, it has introduced alternative ways of capturing images to enable effective visual storytelling on screen. Based on these findings, it recommends that Cinematographers in Ghana should continue to adhere to the conventions and observe protocols to avoid contracting the virus. Also, Cinematographers should accept the situation that we are in the new normal and should further explore current strategies in filming.